2012
DOI: 10.1111/j.1600-0897.2012.01133.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood NK Cell Cytotoxicities are Negatively Correlated with CD8+ T Cells in Fertile Women but not in Women with a History of Recurrent Pregnancy Loss

Abstract: NK cell-mediated immunopathology plays a role in RPL. Women with RPL have a disrupted immune regulation between cytotoxic T and NK cells. Failure of immune modulation by CD8(+) T cells may exert NK cell activation and reproductive failures in women with RPL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
1
16
0
1
Order By: Relevance
“…An increased number of peripheral NK cells is regarded as an important marker for RM . Peripheral blood NK cell activity was significantly decreased during early pregnancy compared to nonpregnant status . These results suggest that the decrease in NK cells and the suppression of NK cell activity may prevent a maternal alloimmune reaction to the fetus.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…An increased number of peripheral NK cells is regarded as an important marker for RM . Peripheral blood NK cell activity was significantly decreased during early pregnancy compared to nonpregnant status . These results suggest that the decrease in NK cells and the suppression of NK cell activity may prevent a maternal alloimmune reaction to the fetus.…”
Section: Discussionmentioning
confidence: 82%
“…NK cells play a critical role in the establishment and maintenance of pregnancy and placental development . Circulating NK cells were found to be elevated both in percentage and cytotoxicity in RM patients . An increased number of peripheral NK cells is regarded as an important marker for RM .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrations of the circulating immune cells have been proposed to be responsible for recurrent miscarriage (RM), unexplained infertility, and repeated implantation failure (RIF). A Th1 cytokine bias, increased NK cell activity, or elevated percentages of peripheral blood lymphocyte subsets has been found with increased prevalence in these patients, compared with normal fertile women, suggesting that the systemic regulation of immune cells is directly related to the reproductive outcome.…”
Section: Introductionmentioning
confidence: 90%
“…Cytokines that are secreted by Th1 cells (e.g., IL-2, TNF-α, IFN-γ) will negatively affect embryonic implantation because trophoblasts are highly sensitive to these cytokines, and this can lead to apoptosis of trophoblast cells [46]. Our preliminary experiments also found that the Th1-type cytokines IL-2 and IFN-γ are highly expressed in the co-culture system of cells that come from the maternal-fetal interface in CBA/J × DBA/2 matings (unpublished data).…”
Section: Discussionmentioning
confidence: 99%